Pemberdayaan Ekonomi Masyarakat Kampoeng Oase Ondomohen Surabaya Melalui Diversifikasi Produk Olahan Ikan Berbasis Urban Farming - Fungki Sri Rejeki; Diana Puspitasari; Shofiya Syidada; Endang Retno Wedowati; Adi Chandra (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance community economic empowerment and strengthen household food security through the diversification of processed fish products based on urban farming. The program was implemented using a participatory approach through five stages: socialization, practice-based training (learning by doing), application of appropriate technology, mentoring and evaluation, and sustainability planning. The partners involved in this activity consisted of 20 members of the Kampoeng Pintar Oase Ondomohen Farmer Group in Surabaya. Evaluation instruments included participant response questionnaires, observations, and activity documentation, which were analyzed using descriptive quantitative and qualitative methods. The results of the program showed an improvement in partners’ capacity to process fish into value-added products. Product variants increased from two types to six processed products, namely nuggets, sempol, fish katsu, fish sticks, shredded fish, and fish sumpia. In addition, the application of packaging technology and digital marketing training improved product quality, shelf life, and market reach, thereby creating the potential to increase community income.